Medicinal Chemistry approach, pharmacology and neuroprotective benefits of CB2R modulators in neurodegenerative diseases. (August 2021) - Ferrisi, Rebecca; Ceni, Costanza; Bertini, Simone; Macchia, Marco; Manera, Clementina; Gado, Francesca
Abstract: In the last decades, cannabinoid receptor 2 (CB2 R) has continued to receive attention as a key therapeutic target in neuroprotection. Indeed, several findings highlight the neuroprotective effects of CB2 R through suppression of both neuronal excitability and reactive microglia. Additionally, CB2 R seems to be a more promising target than cannabinoid receptor 1 (CB1 R) thanks to the lack of central side effects, its lower expression levels in the central nervous system (CNS), and its inducibility, since its expression enhances quickly in the brain following pathological conditions. This review aims to provide a thorough overview of the main natural and synthetic selective CB2 R modulators, their chemical classification and their potential therapeutic usefulness in neuroprotection, a crucial aspect for the treatment of neurodegenerative diseases. Graphical Abstract: ga1